Studi Kepustakaan Kejadian Toksoplasmosis pada Ternak Sapi di Indonesia - Maria Serlyanti Apong; Diana A Wuri; Novalino H. G. Kallau (Jurnal Veteriner Nusantara, 2022)
Toxoplasmosis is a disease caused by Toxoplasma gondii (T. gondii). Cats are the definitive host of T. gondii. The intermediate hosts of this disease are warm-blooded animals, humans are also intermediate hospitals, mammals and poultry groups. This research aims to see the level of toxoplasmosis incidence in cattle and to see the relationship between risk factors and the incidence of toxoplasmosis in cattle. The results of the study show that the data with the highest level is in Lampung Pringsewu district, with a prevalence of 95,8%, while the lowest prevalence data are in West Java Province, Cimahi City which is negative for toxoplasmosis and also in Bali Province, with a prevalence level of 1,59%. Factors contributing to an increase in toxoplasmosis infection are environmental conditions and farm management, sex, age and contact with cats.